The Effect of Diabetes on Lipid Profile in Patients with Type 1 Diabetes - A Mohammed Ali; OA Mahdi Mandalawi; Z Mohammed Latheeth (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Bābul)
Background and Objective: Type 1 diabetes mellitus and its associated comorbidities are regarded as significant health issues. The present research aims to assess the impact of glycemic control on lipid profile of hospitalized patients with type 1 diabetes mellitus and for early diagnosis of dyslipidemia in cases with type 1 diabetes mellitus. Methods: This cross-sectional was conducted at the Pediatric Department of Al-Imamain Al-Kadhmain Medical City from March 2018 to July 2019. Information about the gender and age of the patient, the age of diagnosis and duration of diabetes, insulin therapy: 2-3 times a day, regular blood sugar checking (daily) were collected using a questionnaire. Using American Diabetes Association criteria, cases were separated into excellent and poor glycemic control groups, and lipid profile anomalies were compared. Findings: Out of the total of 128 people present in this study, 86 people (67%) had poor control. Increasing age of patients was associated with poor blood sugar control, so that between the ages of 13 and 18, 47 cases (54.7%) had poor control. It also increased the duration of poorly controlled diabetes. An increase in triglyceride level was evident in 76 people (88.4%), cholesterol in 52 people (60.5%) and low-density lipoprotein in 12 people (14%) among patients with poor control. Conclusion: The results of the present study showed that increasing age and duration of the disease and high levels of triglycerides, cholesterol and low-density lipoprotein are predictors of poor glycemic control in children with type 1 diabetes.